Assessing the Awareness of Public Libraries in Providing Sexualrelated Information for Adolescents - Fauzi, Nur Fadhilah Muhamed; Ismail, Saidatul Akmar; Ahmad, Masitah; Saman, Wan Satirah Wan Mohd (Journal of Informatics and Mathematical Sciences, 2017)
This paper is an attempt to describe the level of awareness among public libraries on their roles, challenges and the effort of the public libraries in providing sexual-related information for adolescents. Since the sexual-related information remains taboo in the context of this study, the public libraries seem not ready to provide such information to their users. In order to gather rich data, a qualitative type of study is chosen. Three participants purposively selected for interview sessions. The participants are librarians who work with public libraries; in charge of library activities. Further analysis shows that generally public libraries in Malaysia are not well prepared or ready to provide sexual related information due to cultural factor.